Fecal contamination level of Cotonou Lagoon waters (Benin, West Africa) - ADJAHOUINOU, Dogbè Clément; LAGNIKA, Moïssou; TOSSAVI, DARIUS; FIOGBE, EMILE DIDIER (My University, 2015)
Surface waters are highly contaminated by solid and liquid wastes coming from anthropogenic activities. Wastewaters thrown out without purification contribute actively to microbiological pollution of these aquatic areas. In the current study, the fecal contamination level of Cotonou lagoon water has been assessed. Six stations have been sampled and fecal pollution indicator bacteria have been numbered using seeding method by incorporation in specific nutritious media. The registered mean bacterial loads were 3.14.103 ± 2.12.103 CFU/100 mL, 1.10.104 ± 7.11.103 CFU/100 mL, 4.03.103 ± 3.82.103 CFU/100 mL and 1.61.103 ± 2.11.103 CFU/100 mL for E. coli, total coliforms, fecal streptococci and anaerobic sulphite reducers respectively. These values have exceeded widely standards recommended for safe recreational waters. Therefore, Cotonou lagoon waters were highly contaminated owing to unchecked discharge of feces and urban effluents. It is urgent to strengthen basic sanitation facilities and undertake the purification of wastewaters before any pouring in order to reduce the fecal pollution level and consequently the hazards linked to public health.
Keywords: Cotonou Lagoon; fecal pollution; wastewater; sanitation; people’s health.